Pengukuran Kinerja Pada Perumdam Tirta Pandalungan Kabupaten Jember - Larosta Putri Inriandi; Endro Sugiartono (Politeknik Negeri Jember, 2023)
This study aims to determine the results of performance measurement at Perumdam Tirta Pandalungan Jember Regency using the Balanced Scorecard measurement method. This research is a qualitative descriptive study. The data source of this research uses primary data by distributing questionnaires and interviews, secondary data by using financial report data and company data. The results of this study indicate that the performance of Perumdam Tirta Pandalungan is measured using the Balanced Scorecard method with a score of 77.08 which is included in very healthy condition with category A.